2021
DOI: 10.3390/nu13030894
|View full text |Cite
|
Sign up to set email alerts
|

Leading Factors for Weight Gain during COVID-19 Lockdown in a Spanish Population: A Cross-Sectional Study

Abstract: The increase in sedentary behaviors during the COVID-19-induced lockdown may have led to a significant weight gain. To investigate this hypothesis, a representative sample of the Spanish adult population comprising 1000 subjects was enrolled in a cross-sectional study between 26 May and 10 June 2020. Computer-assisted telephone interviews were conducted consisting of 29 questions on the topic of lifestyle habits during the lockdown. The cohort comprised 51.5% women and 51% overweight or obese subjects and had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
5
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 47 publications
2
55
5
3
Order By: Relevance
“…Gender is not a consistent predictor of weight gain during COVID-19 self-quarantine, with some studies reporting no gender differences [12,27,37], while others report increased weight gain in women [10,21,25]. Using a Spanish sample, researchers reported that the most critical factor related to weight gain was the female gender, with 58% of women versus 46% of men reporting weight gain during COVID-19 selfquarantine [21]. During COVID-19 self-quarantine, females may have a higher risk than males of atypical sleep levels [72].…”
Section: Gendermentioning
confidence: 99%
See 3 more Smart Citations
“…Gender is not a consistent predictor of weight gain during COVID-19 self-quarantine, with some studies reporting no gender differences [12,27,37], while others report increased weight gain in women [10,21,25]. Using a Spanish sample, researchers reported that the most critical factor related to weight gain was the female gender, with 58% of women versus 46% of men reporting weight gain during COVID-19 selfquarantine [21]. During COVID-19 self-quarantine, females may have a higher risk than males of atypical sleep levels [72].…”
Section: Gendermentioning
confidence: 99%
“…Reports that ran regression models to determine predictors of weight gain during COVID-19 self-quarantine found that both increased television viewing and time spent in sedentary behaviors predicted weight gain [ 8 , 10 , 19 , 20 ]. For instance, in a Spanish sample ( n = 1000), those who gained weight reported that one of the top reasons was decreased physical activity [ 21 ]. Additionally, in a study of 700 Chileans, it was shown that more than 6 hours per day of sedentary time predicted weight gain (OR: 1.85, p = 0.01) while active breaks were associated with weight loss (OR: 0.72, p = 0.04) during the COVID-19 pandemic [ 8 ].…”
Section: Physical Activity Behaviorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies commonly categorised weight gain as an increase greater than 5% of body weight from baseline, 10% for greater increases, 11 or categorised weight gain as an increase of approximately 3 kg above baseline. 12 13 Based on our study population with a mean baseline body weight of 52.3±9.5 (mean±SD), weight change was classified as no significant change (−0.9 to 0.9 kg), mild decrease (−3.9 to −1.0 kg), moderate decrease (−6.9 to −4.0 kg), major decrease (≤−7.0 kg), mild increase (1.0 to 3.9 kg), moderate increase (4.0-6.9 kg) and major increase (≥7.0 kg).…”
Section: Weight Changementioning
confidence: 99%